A new tsunami hazard assessment for eastern Makran subduction zone by considering splay faults and applying stochastic modeling. Issue 1 (2nd January 2023) - Momeni, Payam; Goda, Katsuichiro; Mokhtari, Mohammad; Heidarzadeh, Mohammad
ABSTRACT: Tsunami hazard imposed by possible rupture of splay faults is important as it may significantly intensify tsunami heights locally. The Makran Subduction Zone (MSZ) in the northwestern Indian Ocean can generate large thrust earthquakes that could trigger significant tsunamis. In this paper, the effects of possible rupture of splay faults on the tsunami hazards of eastern MSZ are studied by developing a framework that uses stochastic earthquake rupture models and considers uncertainties related to rupture location, rupture geometry, seismic moment split ratio, earthquake slip asperity location within a fault plane, and earthquake slip heterogeneity. To quantify these uncertainties, 484 different parameter combinations of tsunami sources are considered systematically. The geometry of splay faults is developed using the most recent marine seismic surveys of the tectonic structure of the MSZ. A moment magnitude of 8.6 is considered as a scenario magnitude. The results of this study are generated in two parts, by considering average sources and stochastic sources. Results show significant local amplification of the maximum tsunami heights due to splay faults. For instance, the maximum wave height in Pasni, Pakistan can be amplified by a factor of four due to a single splay fault rupture scenario of average sources.